2021
DOI: 10.1186/s12894-021-00925-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vacuum-assisted sheaths and normal sheaths in minimally invasive percutaneous nephrolithotomy: a systematic review and meta-analysis

Abstract: Background A systematic review and meta-analysis was conducted to compare the safety and efficacy of vacuum-assisted sheaths and conventional sheaths in minimally invasive percutaneous nephrolithotomy (MPCNL) in the treatment of nephrolithiasis. Methods PubMed, Web of Science, Embase, EBSCO, and Cochrane Library databases (updated March 2021) were used to search for studies assessing the effect of vacuum-assisted sheaths in patients who underwent M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As SN-V, SN-V1 and SN-V2 generation tf-URS equipped without a flexible ureteroscope sheath, the back-flow of lavage fluid decreased with high intrapelvic pressure [ 3 ]. When the intrapelvic pressure exceeds 30 mmHg, intrarenal backflow would occur and cause infection [ 18 ]. For patients with infection, it is advised to place double J stent two weeks before surgery when the infection is well controlled [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As SN-V, SN-V1 and SN-V2 generation tf-URS equipped without a flexible ureteroscope sheath, the back-flow of lavage fluid decreased with high intrapelvic pressure [ 3 ]. When the intrapelvic pressure exceeds 30 mmHg, intrarenal backflow would occur and cause infection [ 18 ]. For patients with infection, it is advised to place double J stent two weeks before surgery when the infection is well controlled [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lievore et al found lower rates of infectious complications, shorter OT, and reduced radiation exposure in 104 patients treated with vmPCNL compared to 52 patients who underwent miniPCNL [8]. Recently, a meta-analysis conducted by Zhu et al demonstrated an improvement in safety and efficiency in procedures with a vacuum-assisted sheath compared to those with a conventional sheath [20]. These results highlighted higher SFR while reducing operative time and postoperative infection by using vacuum-assisted technology.…”
Section: Discussionmentioning
confidence: 99%
“…Lievore et al found lower rates of infectious complications, shorter OT and reduced patient's effective dose in 104 patients treated with vamPCNL as compared to 52 patients who underwent miniPCNL [8]. Recently, a meta-analysis conducted by Zhu et al demonstrated an improvement in safety and e ciency in procedures with vacuum-assisted sheath compared to those with conventional sheath [20]. These results highlighted higher SFR while reducing operative time and postoperative infection by using vacuum-assisted technology.…”
Section: Discussionmentioning
confidence: 99%